QUALITATIVE EVALUATION OF ANTIBIOTIC USE WITH GYSSENS METHOD IN PEDIATRIC BRONCHOPNEUMONIA PATIENTS AT ANUTAPURA HOSPITAL - Fajriansyah, Fajriansyah; Arwin, Muh.; Paluseri, Andi; Zulfahmidah, Zulfahmidah (LPPM STIKES BULELENG, 2025)
Bronchopneumonia is still a health problem in Indonesia, with a mortality rate of around 14% for infants aged 1-5 years. Antibiotic therapy with rational use can reduce mortality. Conversely, irrational use of antibiotic therapy will increase the occurrence of resistance which has an impact on increasing morbidity, mortality, and health costs. This study aimed to evaluate the quality of antibiotic use using the Gyssens method in bronchopneumonia patients. This study was an observational study with a qualitative approach conducted at Anutapura Palu Regional General Hospital from January to June 2022. Data were obtained from retrospective searches of patient medical records. Evaluation of antibiotic use was reviewed based on a flowchart of qualitative assessment of antibiotic use with the Gyssens method. There were 52 bronchopneumonia patients who met the inclusion criteria. It was found that 68,66% of patients used rational antibiotics and 31,34% of patients used irrational antibiotics found in class IVa (11,94%), IIIb (4.48%), IIa (11,94%), and IIb (2,98%). In conclusion, the use of antibiotics in half of bronchopneumonia patients is irrational, so efforts need to be made to improve the quality of antibiotic use to avoid morbidity, increased health costs and even death.